One-Bond 13 C- 1 H and 13 C- 13 C Spin-Coupling Constants as Constraints in MA'AT Analysis of Saccharide Conformation - Tetrault, Timothy; Meredith, Reagan J; Zhang, Wenhui; Carmichael, Ian; Serianni, Anthony S (The journal of physical chemistry. B, 2022)
analysis uses ensembles of redundant experimental NMR spin-coupling constants, parametrized -coupling equations obtained from density functional theory (DFT) calculations, and circular statistics to produce probability distributions of molecular torsion angles in solution and information on librational motions about these angles (Meredith et al., . , , 3135-3141). Current DFT methods give nearly quantitative two- and three-bond , , and values for use in analysis of saccharides. In contrast, the accuracy of DFT-calculated one-bond and values is more difficult to determine, preventing their use in modeling. This report describes experimental and computational studies that address this problem using two approaches (Strategies 1 and 2). Differences [ - ] (Strategy 1) ranged from -1.2 to 2.5 Hz, giving an average difference of 0.8 ± 1.7 Hz. Percent differences ranged from -0.8% to 1.6%, giving an average % difference of 0.5 ± 1.1%. In comparison, [ - ] (Strategy 2) ranged from -1.8 to 0.2 Hz, giving an average difference of -1.2 ± 0.7 Hz. Percent differences ranged from -1.2% to 0.1%, giving an average % difference of -0.8 ± 0.5%. Strategy 1 gave an average difference of 2.1 Hz between calculated and experimental values, with an average % difference of 5.1 ± 0.2%. Calculated values were consistently larger than experimental values. Strategy 2 also gave calculated values that were larger than the experimental values, with an average difference of 2.3 ± 0.6 Hz, and an average % difference of 5.6 ± 1.6%. The findings of both strategies are similar and indicate that values in saccharides can be calculated nearly quantitatively, but values appear to be consistently overestimated by ∼5% using current DFT methods.